Synthesis of Novel Quaternary Ammonium Salts and Their in Vitro Antileishmanial Activity and U-937 Cell Cytotoxicity (2016)
ABSTRACT: This work describes the synthesis of a series of quaternary ammonium salts and the assessment of their in vitro antileishmanial activity and cytotoxicity. A preliminary discussion on a structure-activity relationship of the compounds is also included. Three series of quaternary ammonium salts were prepared: (i) halomethylated quaternary ammonium salts (series I); (ii) non-halogenated quaternary ammonium salts (series II) and (iii) halomethylated choline analogs (series III). Assessments of their in vitro cytotoxicity in human promonocytic cells U-937 and antileishmanial activity in axenic amastigotes of L. (Viannia) panamensis (M/HOM/87/UA140-pIR-eGFP) were carried out using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide) micromethod. Antileishmanial activity was also tested in intracellular amastigotes of L. (V) panamensis using flow cytometry. High toxicity for human U937 cells was found with most of the compounds, which exhibited Lethal Concentration 50 (LC50) values in the range of 9 to 46 μg/mL. Most of the compounds evidenced antileishmanial activity. In axenic amastigotes, the antileishmanial activity varied from 14 to 57 μg/mL, while in intracellular amastigotes their activity varied from 17 to 50 μg/mL. N-Chloromethyl-N,N-dimethyl-N-(4,4-diphenylbut-3-en-1-yl)ammonium iodide (1a), N-iodomethyl-N,N-dimethyl-N-(4,4-diphenylbut-3-en-1-yl)ammonium iodide (2a), N,N,N-trimethyl-N-(4,4-diphenylbut-3-en-1-yl)ammonium iodide (3a) and N,N,N-trimethyl-N-(5,5-diphenylpent-4-en-1-yl)ammonium iodide (3b) turned out to be the most active compounds against intracellular amastigotes of L. (V) panamensis, with EC50 values varying between 24.7 for compound 3b and 38.4 μg/mL for compound 1a. Thus, these compounds represents new "hits" in the development of leishmanicidal drugs.